2017
DOI: 10.2196/humanfactors.5110
|View full text |Cite
|
Sign up to set email alerts
|

Personal Communication Device Use by Nurses Providing In-Patient Care: Survey of Prevalence, Patterns, and Distraction Potential

Abstract: BackgroundCoincident with the proliferation of employer-provided mobile communication devices, personal communication devices, including basic and enhanced mobile phones (smartphones) and tablet computers that are owned by the user, have become ubiquitous among registered nurses working in hospitals. While there are numerous benefits of personal communication device use by nurses at work, little is known about the impact of these devices on in-patient care.ObjectiveOur aim was to examine how hospital-registere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 12 publications
1
24
0
Order By: Relevance
“…As noted by the authors, the study contributes to the growing literature addressing the use of mobile technologies in the nursing workplace. Another recent and larger study of registered nurses in hospitals in the United States drew similar results, including concerns about distraction, safety, and policy as well as generational differences in the perception and use of mobile devices (McBride & LeVasseur, 2017). The study thus affirms many of the findings of previous and more recent studies on the topic (McBride & LeVasseur, 2017;Grabowsky, 2015;Planitz, Sanderson, Kipps, & Driver, 2013).…”
Section: Commentarysupporting
confidence: 79%
“…As noted by the authors, the study contributes to the growing literature addressing the use of mobile technologies in the nursing workplace. Another recent and larger study of registered nurses in hospitals in the United States drew similar results, including concerns about distraction, safety, and policy as well as generational differences in the perception and use of mobile devices (McBride & LeVasseur, 2017). The study thus affirms many of the findings of previous and more recent studies on the topic (McBride & LeVasseur, 2017;Grabowsky, 2015;Planitz, Sanderson, Kipps, & Driver, 2013).…”
Section: Commentarysupporting
confidence: 79%
“…Nurses used their smartphones to access information directed at patient care. The most common information sought was related to medications, including drug guides and drug references, in 14 of the 22 (64%) studies reviewed [ 23 , 26 - 31 , 33 - 35 , 37 , 38 , 40 , 43 ]. Nurses reported efficiency of access to medication information; it was easier to search medications by either the generic name or brand name using their smartphones, despite having access to a drug reference book [ 40 ].…”
Section: Resultsmentioning
confidence: 99%
“…Nurses used their smartphones for information seeking for both patient education purposes and for their own educational needs. Out of 22 studies, 4 (18%) reported that nurses used their smartphones for patient education [ 27 , 29 , 33 , 40 ]. Flynn et al [ 27 ] found that more than 75% of the nurses preferred the use of their smartphones to access information for patient education, and this was more commonly noted among nurses between the ages of 18 and 30 years compared to nurses older than 50 years of age.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations